Hyperacusis and plasma levels of cytokines in migraine - Castro, Franciela Massi de; Silva, Aline Vitali da; Bello, Valéria Aparecida; Poli, Regina Célia (Headache Medicine, 2025)
Introduction Migraine is a chronic pain that represents a public health problem and compromises quality of life, with an inflammatory factor involved in its pathophysiology. Objective To verify whether there is an increase in serum cytokines in patients with migraine associated with hyperacusis. Methods The sample consisted of 80 participants in the episodic and/or chronic migraine group, with/without aura, and 80 healthy individuals; aged 18 to 60 years of both sexes. Instruments used: ID-migraine, Migraine Disability Assessment (MIDAS); Short-Form Headache Impact Test (HIT-6), State Trait Anxiety Inventory (STAI) Y1 Y2, Beck Inventory, Allodynia and Hyperacusis Questionnaire; interleukin dosage by flow cytometry. Results The sample was homogeneous for sex, age and race (p>0.05). There was an association between hyperacusis and migraine (p<0.001). 41.2% of patients with migraine had hyperacusis. The majority of the population with migraine had phonophobia (87.8%); photophobia (93.7%); osmophobia (61.5%); episodic migraine (65.4%); prodrome and postdrome in 80% of them; half of them did not have aura (52%) or allodynia (53.2%). Regarding serum cytokine levels, they had higher levels of IL-2 and TNF-α (Mann-Whitney, p<0.001). INF-γ, IL-4, IL-6, IL-10 in plasma did not differ statistically between the control and migraine groups (Mann-Whitney, p>0.05). The association of hyperacusis with cytokines IL-2, IL-4 and TNFA (Mann-Whitney, p>0.05) in migraine patients was observed. Conclusion It was possible to verify that there was a significant difference in plasma cytokine levels between the groups. The increase in inflammatory markers indicates the possibility of complementary treatment, allowing the intervention of other professionals from multi and interdisciplinary teams.